2015
DOI: 10.1016/j.rmed.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index, respiratory conditions, asthma, and chronic obstructive pulmonary disease

Abstract: Background This study aims to assess the relationship of body mass index (BMI) status with respiratory conditions, asthma, and chronic obstructive pulmonary disease (COPD) in a state population. Methods Self-reported data from 11,868 adults aged ≥18 years in the 2012 South Carolina Behavioral Risk Factor Surveillance System telephone survey were analyzed using multivariable logistic regression that accounted for the complex sampling design and adjusted for sex, age, race/ethnicity, education, smoking status,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
2
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 50 publications
2
32
2
4
Order By: Relevance
“…Although our findings for general adiposity and symptoms extend those of prior studies [4850] to U.S. Hispanics, we did not replicate a linear association between BMI and asthma symptoms found in non-Hispanic whites [49]. Further, attenuation of the association of abnormal waist circumference with FVC and FEV 1 , when adjusted for hs-CRP and HDL, suggest that systemic inflammation and metabolic dysregulation, intricately linked to truncal adiposity, drive its association with asthma burden.…”
Section: Discussionsupporting
confidence: 80%
“…Although our findings for general adiposity and symptoms extend those of prior studies [4850] to U.S. Hispanics, we did not replicate a linear association between BMI and asthma symptoms found in non-Hispanic whites [49]. Further, attenuation of the association of abnormal waist circumference with FVC and FEV 1 , when adjusted for hs-CRP and HDL, suggest that systemic inflammation and metabolic dysregulation, intricately linked to truncal adiposity, drive its association with asthma burden.…”
Section: Discussionsupporting
confidence: 80%
“…, Liu et al . ). Several mechanisms have been proposed for this association, including a reduction in lung volume, secretion of inflammatory mediators and an increase in gastro‐oesophageal reflux (Eneli et al .…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have reported that overweight or obesity had a protective effect against mortality in patients with COPD, 6,7,9 while others have reported a worse HRQL, increased severity of dyspnea and frequency of severe exacerbations in obese patients with COPD. [10][11][12] To the best of our knowledge, few studies have explored the relationship between overweight or obesity and the frequency of COPD exacerbations. [12][13][14][15] Therefore, the aim of this study was to examine whether overweight and obesity are associated with the frequency of acute exacerbations in patients with COPD in Taiwan.…”
Section: Introductionmentioning
confidence: 99%